INOVASI PELAYANAN PUBLIK BERBASIS KEARIFAN LOKAL: STUDI BEST PRACTICE DI DAERAH - Samson Laurens (JURNAL BADATI, 2025)
This study examines the implementation of local wisdom-based public service innovation as a strategy for governance transformation in regional areas. Using a qualitative approach and case study methodology, this research analyzes best practices in integrating local wisdom values into digital and conventional public service systems. The findings indicate that public service innovations incorporating local wisdom not only enhance service effectiveness and efficiency but also strengthen cultural identity and increase public trust in government. This study provides theoretical contributions to developing contextual and sustainable public sector innovation models.